Islam, Science, and the Environment: An Application of Ibrahim Kalin’s “Three Views of Science in the Islamic World” (American Journal of Islam and Society, 2025)
Contemporary discussions on Islam and science are highly variegated, often taking on fundamentally opposite assumptions. The remarkable divergence in the basic methods and assumptions underlying publications in this field make any meta-study, or comparison between approaches, nearly impossible. One pragmatic meta-framework of Islam and science that incorporates a wide range of views and provides meaningful distinctions between them is suggested by Ibrahim Kalin. In his chapter titled, “Three Views of Science in the Islamic World,” Kalin identifies three (non-exhaustive) Islamic critiques of science, which he labels as: ‘ethical/puritanical’; ‘epistemological’; and ‘ontological/metaphysical’. Applying Kalin’s framework to contemporary publications on Islam and the environment offers a rich analysis, enabling us to identify attempts at the instrumentalization of Islamic ethics, hermeneutics, and metaphysics, as well as identify contact points between religion and science.